2015
DOI: 10.1039/c5bm00160a
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive polymer–peptide conjugates for adhesive biointerfaces

Abstract: replaced by an exotic amino acid bearing a 3,4-ethylenedioxythiophene ring in the side chain. The incorporation of the peptide at the end of preformed PEDOT chains has been corroborated by both FTIR and X-ray photoelectron spectroscopies. Although the morphology and topology are not influenced by the incorporation of the peptide to the end of PEDOT chains, this process largely affects other surface properties. Thus, the wettability of the conjugates is considerably higher than that of PEDOT, independently of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…The wettability and electrochemical activity of the resulting conjugates were considerably higher than that of PEDOT with higher cell adhesion. The results further indicated that PEDOT promoted the exchange of ions at the conjugate–cell interface while incorporating good thermal properties, good environmental stability in its doped state with fast doping–undoping process . Another electroactive polymer–aminoacid hybrid material has been synthesized by Aleman and coworkers by incorporation of a synthetic amino acid as end‐capping to the conjugating PEDOT chains that have potential applications in cell adhesive biointerfaces .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wettability and electrochemical activity of the resulting conjugates were considerably higher than that of PEDOT with higher cell adhesion. The results further indicated that PEDOT promoted the exchange of ions at the conjugate–cell interface while incorporating good thermal properties, good environmental stability in its doped state with fast doping–undoping process . Another electroactive polymer–aminoacid hybrid material has been synthesized by Aleman and coworkers by incorporation of a synthetic amino acid as end‐capping to the conjugating PEDOT chains that have potential applications in cell adhesive biointerfaces .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The first oligothiophene conjugated to a β‐sheet pentapeptide was reported in 2004. Aleman and coworkers have synthesized an electroactive polymer‐peptide conjugate by combining PEDOT and Arg‐Gly‐Asp (RGD)‐based peptide where Gly has been replaced by an amino acid with 3,4‐ethylenedioxythiophene ring attached to the side chain . The wettability and electrochemical activity of the resulting conjugates were considerably higher than that of PEDOT with higher cell adhesion.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…These results indicate that the PEDOT‐embedded scaffolds might have accelerated adhesion and cell proliferation by either diminishing the antifouling properties of the PEGDM, such that cells would adhere favourably, or through an electrostatic interaction . Furthermore, AFM measurements confirmed that the surface roughness of the electrospun mats was increased after PEDOT deposition (Figure S3), providing another reason for the enhanced cellular adhesion and proliferation on the PEDOT‐embedded scaffolds compared to the pristine NBR/PEGDM fiber mats . The adhered cell morphology and cytoskeletal structure of the seeded cardiac fibroblasts were stained with F‐actin and were imaged 5 days after incubation using a confocal laser scanning microscope (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the pore size, pore structure, material's permeability, and physical/chemical properties not only impact cell proliferation but also can control the direction of cell growth, as has been demonstrated in an artificial nerve guide conduit . It is well known that hydrophilicity/hydrophobicity can be influenced by the surface chemistry, while the roughness ratio and topological structure can also influence the wettability of the surface . Much work has been directed at examining the relationships between the ability for cell proliferation and adhesion as related to conditions of the micropore material in an attempt to identify effective biomaterials that can be used in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…36 It is well known that hydrophilicity/hydrophobicity can be influenced by the surface chemistry, while the roughness ratio and topological structure can also influence the wettability of the surface. 5,37 Much work has been directed at examining the relationships between the ability for cell proliferation and adhesion as related to conditions of the micropore material in an attempt to identify effective biomaterials that can be used in clinical applications. However, the majority of these studies were based on the use of flat films and micropore material surfaces with pore size in excess of 200 lm.…”
Section: Discussionmentioning
confidence: 99%